Fluorescently tagged laminin subunits facilitate analyses of the properties, assembly and processing of laminins in live and fixed lung epithelial cells and keratinocytes - Hopkinson, Susan B. (2008)
Recent analyses of collagen, elastin and fibronectin matrix assembly, organization and remodeling have been facilitated by the use of tagged proteins that can be visualized without the need for antibody labeling. Here, we report the generation of C-terminal tagged, full-length and “processed” (α3ΔLG4-5) human α3 as well as C-terminal tagged, full-length human β3 laminin subunits in adenoviral vectors. Human epidermal keratinocytes (HEKs) and human bronchial epithelial (BEP2D) cells, which assemble laminin-332-rich matrices, as well as primary rat lung alveolar type II (ATII) cells, which elaborate a fibrous network rich in laminin-311, were infected with adenovirus encoding the tagged human laminin subunits. In HEKs and BEP2D cells, tagged, full-length α3, α3ΔLG4-5 and β3 laminin subunits incorporate into arrays of matrix organized into patterns that are comparable to those observed when such cells are stained using laminin-332 subunit antibody probes. Moreover, HEKs and BEP2Ds move over these tagged, laminin-332-rich matrix arrays. We have also used the tagged β3 laminin subunit-containing matrices to demonstrate that assembled laminin-332 arrays influence laminin matrix secretion and/or assembly. In the case of rat ATII cells, although tagged α3 laminin subunits are not detected in the matrix of rat ATII cells infected with virus encoding full-length human α3 laminin protein, processed human α3 laminin subunits are incorporated into an extracellular fibrous array. We discuss how these novel laminin reagents can be used to study the organization, processing and assembly of laminin matrices and how they provide new insights into the potential functional importance of laminin fragments.